Wound and Loss In Naipaul’s India: A Wounded Civilization and an Area of Darkness - Khanal, Babu Ram (Tribhuvan University Journal, 2019)
This study explores the pain and multifaceted loss in Naipaul’s novels: India: a Wounded Civilization and An Area of Darkness. In the first part of this research, pain and loss of the aborigines have been exposed. It challenges the nationalist discourse of the India’s progress. The second part, mapping culture through the novel is divided into two sections. The first section- "India: A Wounded Civilization" deals with the condition of India in the post independent period. It claims that India has been wounded for many centuries of British Raj. The second section follows "An Area of Darkness." Naipaul assumes that India is still in darkness. People are living in illiteracy, ignorance and poverty. In addition to caste system practiced in different communities has shadowed the pure and mounted image of India. The last section is the conclusion of the research. It sums up the whole claims and textual analysis of the research.